Effectiveness of Endoscopic Application of Type I Human Collagen Solution in Treatment of Inhalation Injury - I. E. Galankina; A. V. Makarov; A. V. Mironov; S. V. Smirnov; N. V. Borovkova; I. N. Ponomarev; A. M. Gasanov (Общая реаниматология)
The purpose of the study was to determine the morphological characteristics of the repair process of the tracheal and bronchial mucosa after sanitation bronchoscopy using type I human  collagen solution  in patients with an inhalation  injury (II).Materials and methods.  An open-label, randomized, prospective study included  59 patients with inhalation injury (2—3 severity  degree according  to the classification  of Yu. V. Sinev and A. Yu. Skripal'.  The main group consisted of 29 patients. They underwent a sanitation bronchoscopy using type I human collagen solution applied onto erosive and ulcerative lesions of the mucous membrane.  The reference group consisted  of 30 patients who underwent sanitation bronchoscopy in accordance with the standards of medical care. In order to assess the morphological  dynamics  of the repair process of the mucous membrane,  a morphological  study  of the bioptate obtained during endoscopic studies was carried out. The solution for the application was prepared by acid extraction of type I human collagen from ligaments and tendons as described  earlier (Russian Federation invention patent No. RU 2591544 C1).Results. Complete  epithelization of the tracheal  and bronchial mucosa occurred  significantly  earlier (4 (3; 7) days) in patients with the 2nd  degree inhalation injury when using type 1 collagen application, than in those without the application (7 (4; 9) days) (n=15 and n=21 respectively; U=49.5; P=0.0004). In the case of the 3rd  degree inhalation injury, coating of ulcers of the tracheobronchial tree mucosa with the collagen solution also significantly reduced the epithelialization period on average to 8 (7; 10) days, while after the standard sanitation bronchoscopy, this period was 17 (12; 22) days (n=14 and n=9  respectively;  U=1; P=0.0001). The morphological  changes in patients of the main group were characterized by the absence of signs of a purulent inflammation, early appearance of macrophages and lymphocytes, and covering of type I collagen by simple cuboidal epithelium, while in the reference group, there was a severe purulent inflammation manifested by polymorphonuclear leukocyte  infiltration.Conclusion. The sanitation bronchoscopy with simultaneous closure of the damaged areas of the mucous membrane with the type I human collagen solution  results  in relief of the inflammatory process which is confirmed by morphological  studies.